KOMITMEN ORGANISASI, KARAKTERISTIK INDIVIDU, DAN MOTIVASI KERJA TERHADAP KEPUASAN KARYAWAN (PADA PT. KHARISMA DIAN SUARA MALANG) - Sasqia Lailatul Fahiza; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to discuss and analyze organizational commitment, individual characteristics and work motivation on employee job satisfaction. And to analyze or determine the effect partially or simultaneously on variable X with variable Y. The population used in this study were all employees at PT. Kharisma Dian Suara Malang, which is 40 employees. The method of collecting data uses a questionnaire. The analysis used includes instrument testing, normality test, multiple linear analysis, classic assumption test, and hypothesis. The results of this study indicate that organizational commitment emphasizes employee job satisfaction, individual characteristics that emphasize satisfaction with employees, work motivation emphasizes the importance of employee job satisfaction. So, organizational commitment, individual characteristics and simultaneous cooperation motivation on employee job satisfaction. Keywords: Organizational Commitment, Individual Characteristics and Work Motivation on Job Satisfaction